2019
DOI: 10.1007/s10549-019-05185-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of antidiabetic medication and statins with breast cancer incidence in women with type 2 diabetes

Abstract: Purpose To address the possible association between the use of metformin, other forms of antidiabetic medication (ADM) and statins with the incidence of breast cancer in women with type 2 diabetes (T2D). Methods Data were collected from a Finnish nationwide diabetes database (FinDM). The study cohort consisted of women diagnosed with T2D in 1996–2011 in Finland. In full-cohort analysis, Poisson regression was used to estimate hazard ratios (HRs) in relation to use of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
1
13
0
1
Order By: Relevance
“…And the findings from several observational studies regarding the association between statins use and breast cancer are inconsistent. Murakami et al reported that statin use is inversely associated with the risk of breast cancer [16], while Leung et al showed the opposite finding [17], furthermore some studies found no associations [18,19]. The findings regarding the relationship between statins and the prognosis of breast cancer are also conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…And the findings from several observational studies regarding the association between statins use and breast cancer are inconsistent. Murakami et al reported that statin use is inversely associated with the risk of breast cancer [16], while Leung et al showed the opposite finding [17], furthermore some studies found no associations [18,19]. The findings regarding the relationship between statins and the prognosis of breast cancer are also conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…According to data from the Finnish national diabetes database, 2300 women were diagnosed with BC, and then were treated with metformin, insulin and statins. Case-control analysis clearly showed that there was no difference in cancer incidence between the metformin group (HR = 1.02, 95% CI 0.93-1.11) and the statin group (HR = 0.97, 95% CI 0.89-1.05), while insulin treatment was associated with slightly increased morbidity (HR = 1.18, 95% CI 1.03-1.36) [48].…”
Section: Breast Cancermentioning
confidence: 96%
“…Likewise, research indicates a reduction in morbidity, as well as a more favorable clinical course as a result of the application of drugs, such as metformin, which reduce these factors [58][59][60]. However, the results of the studies on the use of statins in EC remain inconclusive [61][62][63][64][65], and the observational studies often compare the effects of two drugs, i.e., antidiabetic metformin and a selected compound from the statins class [48,49].…”
Section: Endometrial Cancermentioning
confidence: 99%
“…Well-tolerated, commonly used medications for multiple chronic conditions with potential for reducing cancer risk may offer more widespread and sustained use [3][4][5][6]. Metformin, a biguanide used to treat type 2 diabetes, has antiproliferative effects, has been linked to reduced cell growth and circulating estrogen, and has been recommended to reduce the risk of breast cancer recurrence though the evidence is less consistent for incidence [7][8][9][10][11][12][13]. The evidence for statins, HMG-CoA reductase inhibitors used to treat high cholesterol that may reduce the cholesterol available for hormone synthesis and cell proliferation, is stronger but similarly more consistent for recurrence than incidence, and particularly congruous for lipophilic statins [7,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Metformin, a biguanide used to treat type 2 diabetes, has antiproliferative effects, has been linked to reduced cell growth and circulating estrogen, and has been recommended to reduce the risk of breast cancer recurrence though the evidence is less consistent for incidence [ 7 13 ]. The evidence for statins, HMG-CoA reductase inhibitors used to treat high cholesterol that may reduce the cholesterol available for hormone synthesis and cell proliferation, is stronger but similarly more consistent for recurrence than incidence, and particularly congruous for lipophilic statins [ 7 , 14 – 19 ]. Little is known about the combined use of these drugs and breast cancer risk, though combined use can be common in individuals with type 2 diabetes who are at higher risk for cardiovascular disease [ 20 ].…”
Section: Introductionmentioning
confidence: 99%